ACM Proceedings of the 2009 Workshop on Web Search Click Data - Craswell, Nick; Jones, Rosie; Dupret, Georges; Viegas, Evelyne (ACM, 2009)
Proceedings of the 2009 workshop on Web Search Click Data Survey and evaluation of query intent detection methods - David J. Brenes, Daniel Gayo-Avello, Kilian Pérez-González Analysis of long queries in a large scale search log - Michael Bendersky, W. Bruce Croft Distinguishing humans from robots in web search logs: preliminary results using query rates and intervals - Omer Duskin, Dror G. Feitelson Incremental learning to rank with partially-labeled data - Kye-Hyeon Kim, Seungjin Choi Generating unambiguous URL clusters from web search - Smith, T. Brailsford, C. Donner, D. Hooijmaijers, M. Truran, J. Goulding, H. Ashman Topic-specific analysis of search queries - Judit Bar-Ilan, Zheng Zhu, Mark Levene Optimising topical query decomposition - Marcin Sydow, Francesco Bonchi, Carlos Castillo, Debora Donato Search shortcuts using click-through data - Ranieri Baraglia, Fidel Cacheda, Victor Carneiro, Vreixo Formoso, Raffaele Perego, Fabrizio Silvestri Query suggestions using query-flow graphs - Paolo Boldi, Francesco Bonchi, Carlos Castillo, Debora Donato, Sebastiano Vigna Using query logs and click data to create improved document descriptions - Maarten van der Heijden, Max Hinne, Wessel Kraaij, Suzan Verberne, Theo van der Weide Intentional query suggestion: making user goals more explicit during search - Markus Strohmaier, Mark Kröll, Christian Körner Usefulness of quality click-through data for training - Craig Macdonald, Iadh Ounis Comparative analysis of clicks and judgments for IR evaluation - Jaap Kamps, Marijn Koolen, Andrew Trotman Tailoring click models to user goals - Fan Guo, Lei Li, Christos Faloutsos